The Revolving Door for Financial Regulators - Shive, Sophie A.; Forster, Margaret M. (Review of Finance, 2017)
We investigate the motivations and effects of financial firms’ hiring of former US financial regulatory employees. The number of top executives with regulatory experience per firm has increased 24% over 2001–15, and hiring is associated with positive average announcement returns and a salary premium. In the quarter after hire, market and balance sheet measures of firm risk decrease significantly and measures of risk management activity increase, especially for hires from prudential regulators, who directly monitor financial firm risk. The absence of this result for unregulated firms and for exogenous shocks to regulatory experience suggests that firms hire ex-employees of their regulators when they perceive a need to reduce risk, consistent with a schooling hypothesis. We find little direct evidence of quid pro quo behavior in regulatory event frequency and fines.